Modulation of autoimmune rheumatic diseases by oestrogen and progesterone - Hughes, Grant C.; Choubey, Divaker (Nature reviews. Rheumatology, 2014)
Key Points Sexual dimorphism in the risk and expression of human autoimmune rheumatic diseases involves the immunomodulatory effects of postpubertal levels of sex steroid hormones Oestrogen increases the risk of SLE in genetically susceptible women by increasing type 1 interferon production and favouring the survival of B cells that produce pathogenic IgG autoantibodies Progesterone might reduce the risk of SLE in genetically predisposed women by countering these oestrogen effects—thus, the balance between oestrogen and progesterone might influence the risk of SLE Pregnancy-induced amelioration of rheumatoid arthritis probably involves anti-inflammatory and tolerogenic effects of high circulating levels of progesterone, oestrogen and cortisol Research into mechanisms of sex-steroid-related immunomodulation is expected to uncover novel therapeutic targets in autoimmune rheumatic conditions and to improve understanding of sexual dimorphism in risk of other diseases Sex steroid hormones are likely to influence risk and expression of autoimmune diseases through modulation of key immune pathways. In this Review, Hughes and Choubey discuss the immunomodulatory mechanisms behind the sexual dimorphism observed in patients with systemic lupus erythematosus and rheumatoid arthritis, and focus on how oestrogen and progesterone affect manifestation of these diseases. Sexual dimorphism is evident in the risk and expression of several human autoimmune diseases. Differences in disease manifestations observed between sexes are likely to involve immunomodulation by sex steroids, nonhormonal factors encoded by genes on the X and Y chromosomes, and immunological phenomena unique to pregnancy. In systemic lupus erythematosus (SLE), and perhaps other autoantibody-mediated diseases, oestrogen seems to increase the risk of disease in genetically predisposed women by targeting key immune pathways, including the type 1 interferon (IFN) response, differentiation of CD4 + T helper cells and survival of autoreactive B cells. By contrast, progesterone seems to reduce the risk of SLE by counteracting the effects of oestrogen on some of these same pathways, which suggests that the balance between oestrogen and progesterone can determine disease expression. In this Review we focus on the roles of the sex steroid hormones oestrogen and progesterone in modulating the risk and expression of SLE and rheumatoid arthritis. Intensive research in this area promises to identify novel therapeutic strategies and improve understanding of the immunological requirements and complications of pregnancy, and is expected to define the mechanisms behind sexual dimorphism in autoimmunity, immunity and other aspects of human health—a newly announced directive of the NIH.